2009
DOI: 10.1167/iovs.08-1724
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Product (AGE) Accumulation on Bruch’s Membrane: Links to Age-Related RPE Dysfunction

Abstract: AGEs influence ARPE-19 mRNA expression profiles and may contribute to reduced lysosomal enzyme degradative capacity and enhanced accumulation of lipofuscin. Formation of AGEs on Bruch's membrane may have important consequences for age-related dysfunction of the RPE, perhaps leading to age-related outer retinal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 52 publications
2
62
0
2
Order By: Relevance
“…RT-PCR of the RPE and photoreceptor-specific proteins, RPE65 and rhodopsin, demonstrated that there was no contamination of the primary cultured RPE cells with photoreceptors. Expression of TLR3 and TLR4 in ARPE19 cells was subsequently detected by RT-PCR as reported previously (19,28).…”
Section: Abca4mentioning
confidence: 98%
“…RT-PCR of the RPE and photoreceptor-specific proteins, RPE65 and rhodopsin, demonstrated that there was no contamination of the primary cultured RPE cells with photoreceptors. Expression of TLR3 and TLR4 in ARPE19 cells was subsequently detected by RT-PCR as reported previously (19,28).…”
Section: Abca4mentioning
confidence: 98%
“…Seddon et al [45] also reported choriocapillaris dropout beneath the drusen in eyes with early AMD. Accumulated lipid as well as the drusen may be oxidized by exposure to light and oxygen, actually producing reactive byproducts in lipoxidation processes such as advanced glycation end product and malondialdehyde formations [46,47] . Reactive oxygen species damage RPE cells, which is related to the breakdown of the outer blood-retinal barrier and RPE atrophy, possibly exacerbated by smoking and potentially attenuated by antioxidant supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Amadori products undergo subsequent nonenzymatic reactions, including oxidative decomposition, to form a heterogeneous group of modifications known as AGEs (Baynes 2001). The presence of AGEs in aging ocular tissues is well-established (Ishibashi et al 1998;Farboud et al 1999;Hammes et al 1999;Handa et al 1999;Crabb et al 2002a;Howes et al 2004;Glenn et al 2007Glenn et al , 2009). Pentosidine, another AGE in drusen, forms fluorescent lysine -arginine cross-links Glenn et al 2007).…”
Section: Oxidative Protein Modifications In Drusenmentioning
confidence: 99%